Enhancing Babinsa Performance in Jember: The Mediating Role of Public Service Motivation on the Relationship Between Servant Leadership and Work Engagement - Yudha Pradana; Rijalus zeman (HARAMAIN: Jurnal Manajemen Bisnis, 2026)
This study examines the role of public service motivation in mediating the relationship between servant leadership and work engagement in enhancing Babinsa performance in Jember. The research adopts a quantitative approach using Structural Equation Modeling–Partial Least Squares (SEM-PLS) with 226 Babinsa personnel as respondents. Data were collected through structured questionnaires measuring servant leadership, public service motivation, work engagement, and performance indicators. The findings reveal that servant leadership has a significant positive effect on public service motivation and work engagement. Public service motivation also significantly enhances work engagement, indicating that personnel with stronger intrinsic motivation to serve society tend to demonstrate higher levels of enthusiasm, dedication, and involvement in their duties. Furthermore, mediation analysis confirms that public service motivation significantly mediates the relationship between servant leadership and work engagement. The study contributes theoretically by integrating servant leadership theory, public service motivation theory, and work engagement theory within the context of territorial military organizations, which remains underexplored in previous studies. The findings highlight the importance of leadership behaviors emphasizing empathy, empowerment, and ethical responsibility in strengthening personnel motivation and engagement. Practically, this research suggests that Babinsa institutions should develop leadership strategies focused on service orientation and reinforce public service values to improve personnel effectiveness and community trust. Despite its contributions, the study is limited to Babinsa personnel in Jember and employs a cross-sectional design. Future studies are recommended to involve broader contexts and additional organizational variables.